Analisa Perbandingan Aspek Pengukuran Kinerja Keuangan Sebelum dan Masa Pandemi Covid-19 Industri Telekomunikasi di Bursa Efek Indonesia - Muryati Muryati; Akhmadi Akhmadi; Deprianti Deprianti (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2022)
This study aims to determine differences in financial performance from the Solvency and Profitability ratios before and during the covid 19 pandemic. The study was directed to PT Telkomsel. Information is collected using a documentation strategy as financial reports in the first, second and third quarters of 2019 and 2020. The testing strategy uses the Different Test t Test with the Paired Samples t Test, which compares data before the COVID-19 pandemic with data during the COVID-19 pandemic. The results of the review show that Solvency (DER) during the covid 19 pandemic increased compared to before the covid 19 pandemic, while Profitability (ROA) during the covid 19 pandemic decreased compared to before the covid 19 pandemic. Then there were significant differences in financial performance before and during the covid 19 pandemic, both from the Solvency point of view as measured by the Debt Equity Ratio (DER) and from the Profitability point of view as measured by the Return On Assets (ROA) Ratio. The result of the research is that the high Solvency (DER) value and low profitability (ROA) value with this assumption lasting for a long period of time will affect the reduced level of confidence of creditors or potential creditors and investors or potential investors to the company.